Relapse Frequency and Pattern Following Adjuvant Radiotherapy for Intermediate and High-Intermediate Risk Endometrial Cancer Based on Retrospective ESGO-ESTRO-ESP Risk Classification - Kathryn Graham; Laura Hannington; Claire Duncanson; Andrew Wilkinson; Douglas Cartwright; Rosie Harrand; Ashleigh Kerr; Nick Reed; Azmat Sadozye (Clinical and Experimental Obstetrics & Gynecology)
Background: The management of early-stage endometrial cancer (EC) consists of surgery followed by tailored adjuvant therapy, largely based on the risk of loco-regional recurrence. We evaluated the frequency and site of first relapse in patients who received vaginal brachytherapy (VBT) or pelvic external beam radiotherapy (EBRT) for early-stage EC. These data were stratified retrospectively according to the European Society of Gynaecological Oncology–European Society of Radiotherapy and Oncology–European Society of Pathology (ESGO-ESTRO-ESP, 2020) intermediate risk endometrial cancer (IR-EC) and high-intermediate risk endometrial cancer (HIR-EC) classifications. Methods: The central radiotherapy prescribing system within the West of Scotland Cancer Network was analyzed to identify International Federation of Gynaecology & Obstetrics (FIGO) Stage I–II EC patients who commenced VBT, at a dose of 2100 cGy for 3 fractions, and/or EBRT, at 4500 cGy for 25 fractions, between 1st January 2017 and 31st December 2019. Clinical follow-up was conducted until death or for a maximum of five years (data lock 31st December 2022). Imaging was performed if recurrence was suspected. Statistical analysis was implemented using R statistical software (v4.4.1). Results: In total, 282 patients were identified. The median age was 69 years (range: 37–92 years), and the median follow-up was 33 months (range: 0–68 months). Stage distribution: ⅠA (25.2%), ⅠB (57.4%), and Ⅱ (17.4%). The pathology subtype was predominantly endometrioid (93.6%), but 6.4% of patients had non-endometrioid histology with no myometrial invasion. IR-EC patients comprised 51.1% of the series; all received VBT and no adjuvant chemotherapy. The HIR-EC cohort comprised 48.9% of the series; just over half received EBRT, and adjuvant chemotherapy was delivered to 15.9%. By the end of the study, 37 (13.1%) patients had relapsed, and 41 (14.5%) had died, 22/41 (53.7%) of which were attributable to EC. Recurrences were documented in 11.1% of the IR-EC patients and 15.2% of the HIR-EC patients. Vaginal, pelvic, and distant relapses per risk group and treatment were: 2.1%, 7.6%, and 6.9% in IR-EC (VBT-treated), respectively; 3.1%, 16.9%, and 6.2% in the HIR-EC (VBT-treated), respectively; 0%, 6.9%, and 9.6% in the HIR-EC (EBRT-treated), respectively. None reached statistical significance (p = 0.34, Fisher’s exact test). Salvage therapy for locoregional recurrence was performed in 3.5% (10/282) of patients, and virtually all pelvic relapses were symptomatic. Conclusions: Vaginal relapse rates were very low (1.8%). However, pelvic recurrences occurred in 16.9% of the HIR-EC (VBT-treated) patients, suggesting that external beam radiotherapy should be considered to optimize loco-regional control in this group.